2018
DOI: 10.1002/sctm.18-0035
|View full text |Cite
|
Sign up to set email alerts
|

Role of CXCR2 in the Ac-PGP-Induced Mobilization of Circulating Angiogenic Cells and its Therapeutic Implications

Abstract: Circulating angiogenic cells (CACs) have been implicated in the repair of ischemic tissues, and their mobilization from bone marrow is known to be regulated by the activations of chemokine receptors, including CXCR2 and CXCR4. This study was conducted to investigate the role of N‐acetylated proline‐glycine‐proline (Ac‐PGP; a collagen‐derived chemotactic tripeptide) on CAC mobilization and its therapeutic potential for the treatment of peripheral artery diseases. Ac‐PGP was administered daily to a murine hind l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…4 ). On the other hand, the number of mature capillaries 12 , 13 indicated with ILB4-positive vessels 14 undercoated with SMA-positive cell in LM221- and ONO1301-administrated hearts (240.6 ± 15.5 cells/mm 2 ) tended to be higher than that in LM221-administrated hearts (153.8 ± 10.4 cells/mm 2 cells/mm 2 ). In addition, the number of mature capillaries in LM221- and ONO1301-administrated hearts significantly increased compared to that in control hearts (57.9 ± 8.4 cells/mm 2 , p < 0.05) and ONO1301-administrated hearts (83.7 ± 0.7 cells/mm 2 , p < 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…4 ). On the other hand, the number of mature capillaries 12 , 13 indicated with ILB4-positive vessels 14 undercoated with SMA-positive cell in LM221- and ONO1301-administrated hearts (240.6 ± 15.5 cells/mm 2 ) tended to be higher than that in LM221-administrated hearts (153.8 ± 10.4 cells/mm 2 cells/mm 2 ). In addition, the number of mature capillaries in LM221- and ONO1301-administrated hearts significantly increased compared to that in control hearts (57.9 ± 8.4 cells/mm 2 , p < 0.05) and ONO1301-administrated hearts (83.7 ± 0.7 cells/mm 2 , p < 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Recently, new strategies have been developed to increase stem/progenitor cells in the circulatory system. Kwon et al administered daily Intramuscular (IM) injections of Ac-PGP (N-acetyl Proline-Glycine-Proline, a collage-derived chemotactic tripeptide) to a murine model of hindlimb ischemia and evaluated the extent of progenitor cell mobilization (Sca1 + Flk1 + cells)and the effects on ischemic limb reperfusion in a hindlimb ischemia model [ 21 ]. The same investigators had previously shown that this peptide, which is a byproduct of collagen breakdown by Matrix Metalloproteinase (MMP) and prolyl endopeptidases [ 22 ], was able to accelerate wound neovascularization and wound repair by promoting homing and engraftment of exogenous human Endothelial Progenitor Cells (EPCs) in the setting of tissue ischemia [ 23 ].…”
Section: Increase Stem/progenitor Cell Mobilization and Tissue Homingmentioning
confidence: 99%
“…The same investigators had previously shown that this peptide, which is a byproduct of collagen breakdown by Matrix Metalloproteinase (MMP) and prolyl endopeptidases [ 22 ], was able to accelerate wound neovascularization and wound repair by promoting homing and engraftment of exogenous human Endothelial Progenitor Cells (EPCs) in the setting of tissue ischemia [ 23 ]. In their more recent work, IM injections of Ac-PGP improved limb reperfusion, and increased mobilization of progenitor cells [ 21 ]. Zhang et al, have also demonstrated a therapeutic increase in circulating EPCs and enhancement of their homing and angiogenic activity via the administration of recombinant growth differentiation factor-11 (rGDF11) [ 24 ].…”
Section: Increase Stem/progenitor Cell Mobilization and Tissue Homingmentioning
confidence: 99%
“…Recent evidence suggests that vascular repair requires circulating angiogenic cells (CAC), although it has also been shown that highest risk patients have low numbers of poorly migratory CAC . In a recent article in Stem Cells Translational Medicine , Kwon et al investigated the role of N‐acetylated proline‐glycine‐proline (Ac‐PGP) in mediation of angiogenesis, ischemic tissue repair, and mobilization of CAC in a mouse model of hind limb ischemia (HLI) . They found that intramuscular administration of Ac‐PGP into ischemic limbs of surgically induced HLI mice significantly increased angiogenesis and reduced necrosis.…”
Section: Related Publicationsmentioning
confidence: 99%
“…Understanding the specific pathway used by this chemical can shed light on other potential strategies for intervention in the recruitment of stem cells in bone repair. In a related article, Kwon et al examined the use of N‐acetylated proline‐glycine‐proline (Ac‐PGP) to induce mobilization of angiogenic cells to promote revascularization in a mouse model of peripheral arterial disease . Overcoming hurdles of cell mobilization and recruitment is essential for the success of autologous stem cell therapies.…”
mentioning
confidence: 99%